New Testament exegesis a handbook for students and pastors - Fee, Gordon Donald, 1934- (Philadelphia, PA Westminster, 1983)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. -- hermeneutics -- handbooks, manuals, etc